Financial Inclusion of Rural Poor in India - Mr. Showkat Ahmad Teeli; Dr. Imran Mehraj Dar; Dr. Bilal Ahmad Sheikh (Journal of Corporate Finance Management and Banking System, 2023)
The banking industry has continued to use the buzzword "Financial Inclusion" over the past few years. The term is connected with expanding the spread of monetary administrations to the people who don't know about or who are not in that frame of mind to profit monetary administrations because of distant regions or absence of innovation and so forth. The recent reforms carried out in India are in line with the expansion and development of disadvantaged and poor groups. In this regard, PM Modi's slogan, "SABKA SAATH SABKA VIKAS," which aims for everyone's balanced development, is accurate. It won't be possible until corruption and the huge gap between the rich and the poor are reduced. Financial inclusion is about making financial services like banking and insurance available to everyone at reasonable prices. There are not many issues coming in that frame of mind of monetary consideration however it is certain that if some corrective measures are embraced by the specialists, then, at that point, monetary consideration can be accomplished in India without limit. In the end, this will accomplish the campaign's goal of inclusive growth and balanced development. Hence, in present study researcher had analyzed the secondary data from different sources and corresponding findings and suggestions are explained in finding and conclusion section.